Development and evaluation of a wearable motion tracking system, to support hand-tool design - Καρακικές, Μιχαήλ (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Βιομηχανικής Διοίκησης και Επιχειρησιακής Έρευνας, 2017)
Hand-operated tools are part of everyday life for various professions, such as industrial workers, craftsmen, surgeons and physicians. Studies have demonstrated that improper hand tool use can cause discomfort, along with risk for musculoskeletal disorders on the upper extremities. Suitable hand tool design can promote safe use of hand tools and reduce the occurrence of these issues. Among other factors, extreme wrist and forearm posture of the hand tool user is associated with these problems. In this thesis, an inexpensive, wearable system to track wrist and forearm joint motion is developed, using Inertial Measurement Units (IMUs). Its purpose is to be used in hand tool evaluation studies, which examine wrist and forearm posture, and assist in identifying fitting design solutions for hand tools. A methodology for comparing alternative design solutions, using this wearable system, is proposed, through a study on shaving razor handles. In this experimental research, we monitored wrist and forearm motion of subjects using three different razors, and used the results in conjunction with video analysis to (a) determine if a correlation exists between wrist motion and razor handle design, (b) recognize the effect of design features. Results revealed that such correlation does exist. Namely, larger handle length, combined with higher shaving head mobility, led to increased wrist deviation, but decreased forearm deviation from neutral posture. The amplitude of wrist and forearm motion during shaving strokes was found to be independent from the razor used. However, wrist and forearm posture during shaving were not extreme, and the task would not likely cause adverse health outcomes. In conclusion, in order to fully evaluate design solutions of razors, further metrics, both subjective and objective, are needed. Nevertheless, the results do demonstrate how this method can be used to obtain useful information for the design process in hand tools.